TEMPORAL CHANGES IN THE PHYTOPLANKTON COMMUNITY OF THE SOUTHERN BASIN OF LAKE BAIKAL OVER THE LAST 24,000 YEARS RECORDED BY PHOTOSYNTHETIC PIGMENTS IN A SEDIMENT CORE - Tani Y.; Kurihara K.; Nara F.; Itoh N.; Soma M.; Soma Y.; Tanaka A.; Yoneda M.; Hirota M.; Shibata Y. (My University, 2002)
Photosynthetic pigments and other indicators of phytoplankton were analyzed in a dated undisturbed sediment core obtained from the southern basin of Lake Baikal to reveal temporal changes in the phytoplankton community in the lake through the last glacial/post-glacial transition. The sedimentation age of the core spans the last 24 14C ka. Chlorophyll a, its derivatives, carotenoids and total organic carbon (TOC) started to increase after 15 14C ka, and the onset of biogenic silica occurred at 10 14C ka. This indicated that the post-glacial growth of diatoms was preceded by that of other phytoplankton groups. In the record of the pigments and TOC, a temporary decrease was observed in the period 11.5–10.5 14C ka, corresponding to the Younger Dryas cold period. The similarity found between the depth profiles of pyropheophytin a and steryl chlorin esters formed through predation of phytoplankton by zooplankton and that of TOC suggested the important contribution of fecal pellets to sedimentary organic matter in the lake.